Assessment and Correlation of Antimicrobial Resistance and Prostate-Specific Antigen Levels in Prostatitis - Mohamed Eshlak; Emad Elzain; Mohamed Shalouf; Fathallah Salim (Libyan Journal of Medical and Applied Sciences, 2025)
Abstract: The management of prostatitis in resource-limited settings like Libya is challenged by escalating antimicrobial resistance (AMR) and diagnostic limitations. This study characterises bacterial aetiology, resistance patterns, and prostate-specific antigen (PSA) biomarker correlations in Libyan prostatitis patients. A cross-sectional analysis of 72 prostatitis patients at Misurata Medical Centre (2022–2023) was conducted. Expressed urine and prostatic secretions underwent culture and antibiotic susceptibility testing following CLSI guidelines. Total PSA (tPSA), free PSA (fPSA), and f/tPSA ratios were measured using chemiluminescent immunoassay. Predominant isolates were Staphylococcus epidermidis (22.2%), Escherichia coli (19.4%), and Pseudomonas aeruginosa (12.5%). High resistance rates were observed for ceftriaxone (68%) and augmentin (52%), while imipenem maintained 94% susceptibility. The f/tPSA ratio effectively discriminated Gram-negative infections (median 23.5%, IQR: 18–29%) from Gram-positive infections (12.1%, IQR: 8–15%; p < 0.001). tPSA levels correlated with bacterial load (r = 0.58, p < 0.01). This study establishes the first comprehensive resistance profile for prostatic isolates in Libya and validates PSA biomarkers for infection typing. Urgent antimicrobial stewardship programs are needed to address resistance to first-line agents.